Gambaran Pengetahuan Orang Tua tentang Pengaturan Menu Makan Atlet SSB Melalui Fokus Grup Diskusi - Sari, Siska Puspita; Afriani, Yuni; Puspaningtyas, Desty Ervira; Sari, Jihan Novita (Universitas Respati Yogyakarta, 2020)
Athletes need nutritional information accurate sports nutrition for optimal support achievement. In contrast nutrition inadequate, inhibits athletes reached best performance. Focus group discussion about regulating diet to explore the problem in depth parents about nutritional. The provision of food in an athlete should be adapted and with the same period inexercise. Feeding in athelete adapted to the period exercise. Nutrition in athletes divided into three periods. Athletes having different energy needs related to differences in type, intensity, exercise duration. Related the athletes develop, balanced diet necessary requirements. Focus group discussion performed to 24 parent’s atheletes at Sekolah Sepak Bola (SSB) Real Madrid on September 17, 2019 at Universitas Negeri Yogyakarta and performed to 30 parents’s athletes at Sekolah Sepak Bola (SSB) Baturetno on September 15, 2019. Overall, some parents atheletes football know a difference diet in periode exercise. But, paretns athletes not be able to apply diet before, while, recovery peiods exercise because limited knowledge, limited time preparing food, and food habit. Community devotion is expected to be made in a sustainable way. This is due to the possibility of different students each year. In addition to education to parents, activities of this devotion is expected to be done not only to parents, but SSB Real Madrid UNY and SSB Baturetno to athletes and also coach soccer athletes.Keywords: focus group discussion, athlete’s parents, food patern